Root distribution and morphology in some banana (Musa xparadisiaca) varieties - MURTHY, S V KESHAVA; IYENGAR, B R V (The Indian Journal of Agricultural Sciences, 2013)
To lend spatial dimension to nutrient acquisition, the desirable characters are the root-related parameters like rootmorphology, relative root density in sectoral volumes around the plant, total root biomass and length/plant and proportionof thick, medium and thin roots in total root biomass and length. A study was conducted in 6 leading varieties of banana (Musa xparadisiaca L.),.viz 'Dwarf Cavendish' , 'Robusta' (AAA), 'Nendran' (ABB), 'Monthan' (ABB), 'Rasabale' (AAB) and 'Elakki' (AB), during vegetative, flower initiation, shooting and post-shooting stages of plantgrowth. These paramaters were studied using core sampling of soil in a spatial geometry around the plant, extending upto 125 cm radial distance and 40 cm depth. The thin roots of 'Robusta' , 'Rasabale' and 'Monthan' had smaller root radius, and specific root length of all the varieties decreased gradually from vegetative to post-shooting stage of plantgrowth. The growth stages differentially influenced the mean or sectoral root density and relative proportion of roots ofdifferent sizes in total root biomass and length of different varieties. 'Rasabale' and 'Robusta' had higher root densityand total root biomass/plant throughout the growth period. All the varieties had higher root density nearer the plant, which decreased during later stages of plant growth. However, all the varieties also had higher root density in the surface layer, which gradually increased with each growth stage.